Future law emerging technology, regulation and ethics - Edwards, Lilian; Schäfer, Burkhard (Law teacher); Harbinja, Edina (Edinburgh University Press, 2020)
How will law, regulation and ethics govern a future of fast-changing technologies? Bringing together cutting-edge authors from academia, legal practice and the technology industry, Future Law explores and leverages the power of human imagination in understanding, critiquing and improving the legal responses to technological change.